Pemodelan Kapasitas Sungai Air Bayas di Kecamatan Kemuning Kota Palembang dengan Pendekatan HEC-RAS - Ridhuan, Ridhuan; Nisumanti, Sartika; Baniva, Ratih (Universitas Batanghari Jambi, 2025)
Palembang is a city that often experiences flooding which is detrimental to the community.. Flooding can occur for various reasons, including drainage systems that often do not function properly, a lack of water absorption areas in large cities, and rivers that can no longer accommodate the volume of water during heavy rain. One of the rivers in the city of Palembang, namely the Bendung River, is located in the Kemuning District. The problem with this river is that it has many tributaries contributing to its main flow. The purpose of this research is to analyze hydrology, with rainfall data analyzed using normal distribution, log-normal, log-Pearson III, and Gumbel methods. The results of the research conducted on the Air Bayas River showed the flood discharge values for different return periods: 2-year return period: 9.317 m³/s, 5-year return period: 10.552 m³/s, 10-year return period: 11.364 m³/s, 25-year return period: 12.386 m³/s, 50-year return period: 13.147 m³/s, 100-year return period: 13.910 m³/s. The ideal dimensions of the channel with a depth of 2.35 m and a planned width of 6 m are necessary to accommodate the flood discharge without overflowing.